Youth, class, and happiness. (April 2019) - Shoshana, Avihu
Abstract: Through in-depth interviews with youth from different socioeconomic (SES) classes, this article examines how they talk about happiness, how they experience and act in relation to it, and whether and how class-related cultural repertoires affect subjective definitions of happiness. The study's findings reveal significant differences between the various classes with regard to the definition of the concept of happiness, specific characteristics of happiness, the orders of discourse that support happiness-talk, and practices for achieving happiness. Ways in which SES-related cultural repertoires influence the differences in the youths' descriptions are discussed, as well as the implications of these findings for therapeutic and educational work with youth. One of the key findings is the relative absence of use of psychological discourse among low SES youth and its hyper-use among upper SES youth. These findings thus highlight a need for culture-sensitive therapy and education to enhance the daily experiences of schoolchildren. Highlights: This study emphasizes that qualitative and phenomenological research about happiness is required, especially among children and adolescents. A complex understanding of the influence of cultural repertoires related to socio-economic status is also required for subjective definitions of happiness. Youth from different economic classes define happiness, and work towards achieving it, differently.